The Effectiveness of The Virtual Lab-Assisted Guided Discovery Learning Model on Students’ Science Process Skills - Azhar, Azhar; Irianti, Mitri; Rahmadhani, Millinia (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
This study aims to determine students’ science process skills after using the guided discovery model assisted by the virtual PhET lab on vibration and wave materials and the effectiveness of applying the guided discovery learning model assisted by the virtual PhET lab. This research was conducted at a junior high school, SMPN 2 Siak. The research method used is quasi-experimental with a posttest-only control group design. The sample of this study is the experimental class and the control class. Each class has 33 students. The research data was obtained by using a science process skill test instrument. The results showed that the average process skills of the experimental class = 76.76 and the control class = 57.23. The results of the t-test using SPSS software were obtained with (sig) 0.000 < 0.05 . It was concluded that the guided discovery learning model assisted by the virtual lab PhET was more effectively used to improve students’ process skills.